Untargeted metabolomics reveals the impact of Liraglutide treatment on metabolome profiling and metabolic pathways in type-2 diabetes mellitus - Hicham Benabdelkamel; Rajaa Sebaa; Reem H. AlMalki; Afshan Masood; Assim A. Alfadda; Anas M. Abdel Rahman (Elsevier, 2024)
Liraglutide, a type2 diabetes mellitus (T2DM)-related treatment, improves glycemic control and reduces the risks of adverse cardiovascular events in T2DM patients. However, the underlying mechanisms of the above-mentioned beneficial effects of Liraglutide are not well understood. To have better understanding of these mechanisms, we aimed to study the metabolic impacts of Liraglutide on the metabolome and corresponding pathways in T2DM patients, especially metabolism plays a very fundamental role in health and diseases and is influenced by drugs. In this study, plasma samples collected from T2DM patients (n = 20) and taken pre- and post-Liraglutide treatment were used for untargeted metabolomics analyses, including metabolome profiling and metabolic pathway/network analyses. The metabolome profiling analyses identified 93 endogenous metabolites that were significantly affected by Liraglutide treatment where 49 and 44 metabolites were up and down regulated, respectively. Liraglutide caused metabolic alterations impacting metabolic pathways such as pentose and glucuronate interconversion and alanine, aspartate and glutamate metabolism in T2DM patients. Since the last-mentioned pathways are affected by Liraglutide, it could explain partially the overall beneficial effects of Liraglutide in T2DM, especially that glucuronate interconversion pathway is known by its important roles in eliminating toxic and undesirable substances from the human body to maintain good health status. In addition, the metabolism of amino acids induced by Liraglutide could improve the function of immune cells, strengthening the immunity of T2DM patients. Also, Liraglutide induced the level of other metabolites that help in the defense mechanism against oxidative events. Overall, the findings of this study provide a deeper understanding of the underlying mechanisms involved in the beneficial effects of Liraglutide in T2DM from the metabolic aspect.